Development of a mechanism for implementation of a national innovative policy in the energy sector based on Industry 4.0 - Trofymenko, Olena (Technology audit and production reserves, 2021)
The object of research is the processes of formation and implementation of mechanisms for innovative development of the energy sector of the national economy in the context of the fourth industrial revolution. It was determined that at the global level, mechanisms for innovative development of industry and energy are formed in the New Industrial Strategy of the European Union (EU), the Paris Climate Agreement, and the fourth energy package of the EU. The challenges of Industry 4.0 necessitate the formation and adaptation of these mechanisms in individual countries to ensure the innovative development of the energy sector in different countries. In the course of the study, the scientific and applied foundations of ensuring the development of the energy sector at the state level have been analyzed. They also used a system-functional approach, methods of structural and functional analysis and functional synthesis, critical analysis of regulatory framework, goals and objectives in the energy sector of the national economy. As a result, a comprehensive mechanism for the implementation of the national innovation policy in the energy sector of the national economy at various levels of the social hierarchy has been proposed. In particular, 5 functional components of the innovative development of the energy sector of the national economy have been identified: 1) productivity of innovation; 2) effectiveness of innovation policy; 3) effectiveness of energy innovation; 4) investment support for innovative development of the energy sector; 5) development of human capital in terms of decarbonization of the economy. On the basis of these components, the main mechanisms have been formed, which make up a comprehensive mechanism for implementing the state policy of innovative development of the energy sector of the national economy, and each of these mechanisms has its own set of implementation tools: economic; motivational; organizational-technological and political-legal. This forms the basis for the implementation of its interfunctionality and ensures its functioning, based on the principle of multilevel (elements relate to the supranational, interstate, national, regional, local and sectoral levels) and is intended to enhance the socio-economic effects of Industry 4.0.